Saint Lucia. Annual report 2007 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
This report details the results of the actions of the Inter-American Institute for Cooperation on Agriculture to help the Government and other stakeholders in agriculture and related sectors respond to various challenges. Recognizing that business development is inextricably linked to participation in the decision-making process, the Office in Saint Lucia improved the knowledge capacity of MALFF and the leaders of the cooperative sector through training. A framework project for Agribusiness development to include rural business development, and access to credit. The Office also supported MALFF's efforts to consult with industry leaders in agriculture and related sectors to reach an agreement on the development of a marketing infrastructure targeting non-banana producers.